Nature and causes of savings behaviour : Evidence from Tamil households in Jaffna district - Kamalakumari, K. (My University, 2020)
Nature of the saving behaviour of Jaffna Tamil Households has been exhibiting notable changes during the last decade after the war. No study in the District level, conducted in the post war period, explored the causes of savings by incorporating demographic, economic, and psychological determinants. This study aims to fill the methodological, literature and knowledge gap exist between the contributions of demographic, economic determinants towards explaining the variations in household saving behaviour and under-researched psychological determinants. Cross sectional data via survey method, complemented with interviews from 500 Tamil households selected via multi- stage, stratified, quasi random sampling method, consisting of five job categories in Jaffna District is used to test the hypothesis that saving varies across demographic, economic, and psychological determinants. With a main research question to investigate if and to what extent the demographic, economic, and psychological variables explain differences in household saving behaviour across different regions, it is unpacked into three subsidiary questions: they examined the nature, causes and went further to analyze the level, association and impact of these determinants on saving behaviour. By employing Correlation, Multiple regression, Kuruskal- Wallis test, Jonckheere – Terpstra test, Analysis of variance (ANOVA), and Factor analysis (FA), it is found that Economic determinants are more robust in explaining saving behaviour. Demographic determinants moderate or enhance saving depending on the nature of association; Psychological determinants contribute marginally but significantly via the generated factors; Cultural influence is on all variables- their level, association and contributions; Life cycle model do not hold due to differences in motives. The policy implication of this study highlights that financial institutions and development programs should consider psychological variables while designing saving instruments and targeting different social groups. Since households’ financial decisions also help to understand borrowing behaviour, this study proposes social welfare policies for bad debt prevention through educational training. This cross-sectional study provides a snapshot of the saving behaviour, longitudinal studies and recommended to identify the dynamics that took place among Tamil households.
Keywords: Demographic determinants; Economic determinants; Psychological determinants; Saving behaviour; Saving motives